2020
DOI: 10.3238/arztebl.2020.0126
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar Pruritus—Causes, Diagnosis and Therapeutic Approach

Abstract: I n Germany, 17% to 23% of the population suffer from chronic (≥ 6 weeks) pruritus of the skin (1, 2). In 5% to 10% of cases, the female genitalia-and in particular the vulva-are affected (3-6). Thus, vulvar pruritus is a common symptom which often significantly impairs the patient's quality of life. The underlying pathophysiological mechanisms are not yet fully understood. In the past, itching was generally considered to be a subtype of pain sensations. Today, however, it is assumed that it is an independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 83 publications
1
15
0
2
Order By: Relevance
“…In a study that surveyed 480 women from the general population in Boston, Massachusetts, 6.6% of women reported experiencing vulvar itch or burning ( 1 ). This is similar to rates of vulvar pruritus reported amongst the general German population, which was noted to range from 5 to 10% ( 2 ). The true prevalence of vulvar pruritus may be difficult to assess as it is likely underreported given the embarrassment many women feel when discussing genital symptoms ( 3 ).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In a study that surveyed 480 women from the general population in Boston, Massachusetts, 6.6% of women reported experiencing vulvar itch or burning ( 1 ). This is similar to rates of vulvar pruritus reported amongst the general German population, which was noted to range from 5 to 10% ( 2 ). The true prevalence of vulvar pruritus may be difficult to assess as it is likely underreported given the embarrassment many women feel when discussing genital symptoms ( 3 ).…”
Section: Introductionsupporting
confidence: 88%
“…In adult women, vulvovaginal candidiasis is a frequent cause of vulvar pruritus, with some studies suggesting candidiasis accounts for 35–40% of vulvar itch cases in this age group ( 2 ). Multiple epidemiologic studies have indicated that Candida albicans is responsible for the excess of episodes of vulvovaginal candidiasis, although reports indicate than non- albicans Candida species, notably Candida glabrata , account for 10–20% of episodes in certain regions ( 61 – 63 ).…”
Section: Pruritic Vulvar Dermatosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic (≥6 weeks) skin pruritus troubles about 20% of Europeans; in 5% to 10% of them, the itching involves the vulva and female genitalia [1]. After candidiasis, the most common causes of vulvar pruritus are chronic dermatoses, including vulvar lichen sclerosus (VLS), vulvar lichen planus (VLP), and vulvar eczema [1].…”
Section: Introductionmentioning
confidence: 99%
“…Diese tritt mit einer Prävalenz von bis zu 40 % zwar häufig auf, darüber hinaus gibt es jedoch eine Vielzahl an Erkrankungen, die ebenfalls vulvären Juckreiz verursachen können. Aufgrund der multifaktoriellen Genese ist ein interdisziplinärer Therapieansatz besonders wichtig [1].…”
unclassified